ESTEEM Journal of Social Sciences and Humanities: Volume 9, No 1, April 2025 / Noor Ashikin Basarudin … [et al.] - Basarudin, Noor Ashikin; Mohd Azhari, Nor Khadijah; Thominathan, Santhanamery; Ahmad, Azhar; Vijayarajoo, Angeline Ranjethamoney (Universiti Teknologi Mara Cawangan Pulau Pinang, 2025)
On behalf of the ESTEEM Journal of Social Sciences and Humanities (EJSSH) Editorial Team, I am delighted to present Volume 9, No 1, April 2025. After multiple series of the double-blind peer review process, we accepted 11 high-quality manuscripts that met the standard empirical paper requirement and were successfully published. For the next issue, we are looking forward for more insightful and thought-provoking articles from distinguished authors across various disciplines in social sciences and humanities. We welcome international-based papers across countries, regions, and continents that align with these important global objectives focusing on Sustainable Development Goals. We extend our heartfelt gratitude to the authors, reviewers, and our editorial team members for their invaluable contributions in bringing this edition to fruition. We hope you find this journal issue both informative and inspiring, and we look forward to your continued support and engagement.